Kidney Function and Incident Stroke and Dementia Using an Updated Estimated Glomerular Filtration Rate Equation Without Race: The Multi-Ethnic Study of Atherosclerosis - Samuel R. Moen; Jeffrey R. Misialek; Timothy M. Hughes; Craig W. Johnson; Mark J. Sarnak; Sarah N. Forrester; W.T. Longstreth, Jr.; Mercedes R. Carnethon; James S. Pankow; Sanaz Sedaghat (Kidney Medicine)
Rationale & Objective: Equations for estimated glomerular filtration rate (eGFR) have previously included a coefficient for African American race. We evaluated and compared risk of incident stroke and dementia between old and new equations of eGFR for African American and non-African American participants. Study Design: Prospective observational study. Setting & Participants: Baseline values were collected from 6,814 participants in the Multi-Ethnic Study of Atherosclerosis (MESA) cohort between 2000 and 2002. Participants were followed up until 2018. The analytic sample consisted of 6,646 participants (mean [SD] age 62 [10] years; 53% female; 39% White, 27% African American, 12% Chinese American, and 22% Hispanic/Latino). Exposure: eGFR equation from 2021 based on serum creatinine and cystatin C levels without race. Outcome: Incident stroke and dementia. Analytical Approach: Cox proportional regression adjusting for demographic, lifestyle, and clinical variables was performed to estimate associations between different eGFR measures and risk of incident stroke and dementia. Results: During a median follow-up period of 17 years, 349 (5.3%) participants experienced an incident stroke event, and 574 (8.6%) participants experienced incident dementia. In the fully adjusted model, overall participants with eGFR <60 compared with those >90 mL/min/1.73 m2 were at significantly increased risk of dementia (HR, 95% CI: 1.73, 1.21-2.45). A lower eGFR was not significantly associated with incident stroke (1.30, 0.75-2.24). African American participants tended to be reclassified to a lower group of eGFR in the new equations, whereas non-African American participants were reclassified to a higher group of eGFR. When comparing older versus newer equations of eGFR in African American and non-African American participants in association with incident stroke and dementia, differences were minimal. Limitations: Incident dementia was ascertained through International Classification of Diseases (Ninth and Tenth Revisions) codes. Conclusions: Our findings illustrate participants with 2021 eGFR < 60 compared with those with eGFR > 90 mL/min/1.73 m2 have higher risk of dementia in both African American and non-African American participants, but not of stroke. Plain Language Summary: Existing research has established that declined kidney function is associated with stroke and dementia. Kidney function is commonly estimated using inputs of blood proteins alongside demographic inputs of age, sex at birth, and race. Inclusion of race to estimate kidney function has gained increased scrutiny given its problematic nature of being a societal construct rather than an inherent biological trait that affects function of the kidneys. Recommendations were recently made to remove race from this estimation, and data were lacking on the relationship between new estimates of kidney function with outcomes such as stroke and dementia. Our research provides updated risk estimates for stroke and dementia using the new estimation for kidney function in a large multiethnic cohort.